Let's perform: Making literature education alive - Abdul Halim, H. (2008)
The benefits of using performance in literature education are well documented. However, many teachers are hesitant to implement them in their classrooms. Commonly, this is because these teachers feel they don't know enough about how to fairly assess a student's performance (Airasian, 1994). This paper delineates and discusses strategies for making literary texts accessible by appealing to the learner's imagination, as well as to develop insights related to the use of performance in literature education. The aim is to go beyond the choice of handy, traditional theatre scripts of monologues and to make any genre of literature more "dramatic" by looking for the basic ingredients usually associated with a theatrical performance. This will include the use of various performance activities including readers' theatre, choral reading, jazz chants, puppetry, dramatization, story telling, role play as well as spontaneous improvisations. The study use a qualitative approach to deepen the understanding of the participants experience and perceptions of using performance to activate meaning with various interpretation of the texts.